72.9k views
23 votes
Find the distance between (1, 3) and (-2, -6) and put it in simplest radical form

User DreamTeK
by
5.3k points

2 Answers

6 votes

Answer:


  • \tt 9.48

Explanation:

(1,3) and (-2,-6)


\tt Distance= √((-6-3)^2+(-2-1)^2)


\tt =√(9^2+3^2)


\tt =√(81+9) =√(90)


\tt Distance=√(90) =9.48

User Arun Palanisamy
by
5.2k points
7 votes

Answer:


D=√(90)\ or\ D=9.49

Explanation:


D=√((x_2-x_1)^2+(y_2-y_1)^2)\\\\D=√((-2-1)^2+(-6-3)^2)\\\\D=√((-2-1)^2+(-6-3)^2) \\\\D=√((-3)^2+(-9)^2) \\\\D=√(9+81) \\\\D=√(90)\\\\D=9.49

Hope this helps!

User Alberto Scampini
by
5.6k points